2019
DOI: 10.4269/ajtmh.18-1008
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Paracoccidioidomycosis in Solid Organ Transplantation: Disseminated Disease in a Liver Recipient and Literature Review

Abstract: Paracoccidioidomycosis (PCM) is an endemic systemic mycosis that is of great importance in Latin America. Its occurrence in solid organ transplantation (SOT) is rare, but with high mortality rate. In this report, we describe a case of PCM in a liver transplant recipient 19 months after transplantation. The patient presented with multiple skin abscesses, arthritis, osteolytic lesions, and pulmonary and adrenal involvement. Despite the presence of disseminated disease and the patient's immunosuppressed condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…35,[48][49][50] There are only 11 cases reported in solid organ transplantation, but as organ transplantation becomes more available in endemic areas of PCM, awareness of PCM pre-and posttransplant is important, as is investigation of PCM in cases of chronic granulomatous disease. [51][52][53][54][55][56][57][58] In the same way, the use of immunobiological therapy has been growing, and cases of PCM during its use have been reported. 59,60 Case series and isolated case reports suggest that cancer occurs in 0.6 to 11% of patients with PCM, mainly carcinomas of the respiratory and digestive tract, which share the same risk factors as PCM, that is, smoking and alcoholism.…”
Section: Eco Epidemiologymentioning
confidence: 99%
“…35,[48][49][50] There are only 11 cases reported in solid organ transplantation, but as organ transplantation becomes more available in endemic areas of PCM, awareness of PCM pre-and posttransplant is important, as is investigation of PCM in cases of chronic granulomatous disease. [51][52][53][54][55][56][57][58] In the same way, the use of immunobiological therapy has been growing, and cases of PCM during its use have been reported. 59,60 Case series and isolated case reports suggest that cancer occurs in 0.6 to 11% of patients with PCM, mainly carcinomas of the respiratory and digestive tract, which share the same risk factors as PCM, that is, smoking and alcoholism.…”
Section: Eco Epidemiologymentioning
confidence: 99%
“…Although the prevalence is higher in kidney transplantations, liver and lung receivers are at higher risk 2,4,5 . A Brazilian study collected 102 autopsy samples from renal transplants and found the PMC in four individuals, being the described cause of death in one of them 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Paracoccidioidomycosis (PMC) is a systemic fungal disease prevalent in Latin America, with the majority of cases found in Brazil 1,2 . It is caused by thermally dimorphic fungi from Paracoccidioides brasiliensis (P. brasiliensis) and Paracoccidioides lutzii (P. lutzii) complexes, with the last one being described in Brazil's North and Midwest regions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations